ANALYSIS OF BATOPANG (BIOINSECTICIDE OF BROTOWALI STEM EXTRACT AND KETAPANG LEAVES) BASED ON SNI 02-3128-1992 AND EFFECTIVENESS TEST AGAINST WOOD GRASSHOPPER (VALANGA NIGRICONIS) WITH THE METHOD LETHAL CONCENTRATION 50 - Muhamad Aditya hidayah (JARES (Journal of Academic Research and Sciences), 2021)
This research is an experimental study where the variables in this study are divided into three categories, independent, dependent, and confounding variables. From this research, qualitative data and quantitative data were obtained. The qualitative data includes the results of the phytochemical screening test. The quantitative data includes pH test, bioinsecticide effectiveness test, and preservative effectiveness test. Based on the results of the phytochemical analysis, it shows that ketapang and brotowali leaf extracts contain secondary metabolites in the form of saponins, flavonoids, alkaloids, and tannins. The bioinsecticide with the best formulation is the bioinsecticide with a formula of 15% extract because it has an LC50 value that is close to the LC50 value of the probit regression, which is 13.05%. Based on the results, it shows that the bioinsecticide of ketapang leaves and brotowali stems for all formulas has met the quality qualifications according to the requirements in SNI 06-0475-1996.